Leukocyte-Expressed β2-Adrenergic Receptors Are Essential for Survival After Acute Myocardial Injury. Issue 2 (12th July 2016) - Grisanti, Laurel A.; Gumpert, Anna M.; Traynham, Christopher J.; Gorsky, Joshua E.; Repas, Ashley A.; Gao, Erhe; Carter, Rhonda L.; Yu, Daohai; Calvert, John W.; García, Andrés Pun; Ibáñez, Borja; Rabinowitz, Joseph E.; et al.
Abstract : Background: Immune cell–mediated inflammation is an essential process for mounting a repair response after myocardial infarction (MI). The sympathetic nervous system is known to regulate immune system function through β-adrenergic receptors (βARs); however, their role in regulating immune cell responses to acute cardiac injury is unknown. Methods: Wild-type (WT) mice were irradiated followed by isoform-specific βAR knockout (βARKO) or WT bone-marrow transplantation (BMT) and after full reconstitution underwent MI surgery. Survival was monitored over time, and alterations in immune cell infiltration after MI were examined through immunohistochemistry. Alterations in splenic function were identified through the investigation of altered adhesion receptor expression. Results: β2 ARKO BMT mice displayed 100% mortality resulting from cardiac rupture within 12 days after MI compared with ≈20% mortality in WT BMT mice. β2 ARKO BMT mice displayed severely reduced post-MI cardiac infiltration of leukocytes with reciprocally enhanced splenic retention of the same immune cell populations. Splenic retention of the leukocytes was associated with an increase in vascular cell adhesion molecule-1 expression, which itself was regulated via β-arrestin–dependent β2 AR signaling. Furthermore, vascular cell adhesion molecule-1 expression in both mouse and human macrophages was sensitive to β2 AR activity, and spleens from human tissue donors treated with β-blocker showed enhanced vascular cell adhesion molecule-1 expression. The impairments in splenic retention and cardiac infiltration of leukocytes after MI were restored to WT levels via lentiviral-mediated re-expression of β2 AR in β2 ARKO bone marrow before transplantation, which also resulted in post-MI survival rates comparable to those in WT BMT mice. Conclusions: Immune cell–expressed β2 AR plays an essential role in regulating the early inflammatory repair response to acute myocardial injury by facilitating cardiac leukocyte infiltration. Abstract : Supplemental Digital Content is available in the text.